Genetic Transformation of Recalcitrant Upland Switchgrass Using Morphogenic Genes - Xu, Nuoya; Kang, Minjeong; Zobrist, Jacob D.; Wang, Kan; Fei, Shui-zhang (Frontiers in Plant Science, 2022)
Switchgrass (Panicum virgatum) is an excellent feedstock for biofuel production. While genetic transformation is routinely done in lowland switchgrass, upland cultivars remain recalcitrant to genetic transformation. Here we report the establishment of an efficient and reproducible transformation protocol for two upland cultivars, ‘Summer’ and ‘Blackwell’, by ectopic overexpression of morphogenic genes, Baby boom (Bbm) and Wuschel2 (Wus2). Two auxotrophic Agrobacterium strains, LBA4404Thy- and EHA105Thy-, each harboring the same construct containing ZmBbm, ZmWus2, and a green fluorescence protein (GFP) gene, ZsGreen1, were used to infect leaf segments derived from in vitro grown seedlings. The Agrobacterium strains also contain a transformation helper plasmid that carry additional copies of Agrobacterium virulence genes. GFP-expressing calli were identified and selected for regeneration. The highest transformation efficiency of 6% was obtained for the tetraploid cultivar Summer when LBA4404Thy- was used for infection, which is twice of that for the octoploid cultivar Blackwell. LBA4404Thy- consistently outperformed EHA105Thy- on transformation frequency across the two cultivars. Fifteen randomly selected putative transgenic plants of Summer and Blackwell, representing independent callus events, were confirmed as transgenic by the presence of the transgene, ZmAls, and the absence of AtuFtsZ, a chromosomal gene specific to the Agrobacterium strain LBA4404 using polymerase chain reaction. Transgene integration and expression was further confirmed by the detection of GFP in roots, and the resistance to herbicide injury to leaves of select putative transgenic plants. The ZmBbm and ZmWus2 genes were successfully removed from 40% and 33.3% of the transgenic plants of Summer and Blackwell, respectively, via the Cre-Lox recombination system upon heat treatment of GFP-expressing embryogenic calli. Our successful transformation of recalcitrant upland switchgrass provides a method for gene function analysis and germplasm enhancement via biotechnology.